Physical and Functional Outcomes of Simultaneous Vascularized Lymph Node Transplant and Lymphovenous Bypass in the Treatment of Lymphedema. Issue 1 (19th May 2022) - Garza, Rebecca M.; Beederman, Maureen; Chang, David W.
Abstract : Background: The authors analyze the outcomes of simultaneous vascularized lymph node transplant and lymphovenous bypass for treatment of primary and secondary lymphedema. To the best of their knowledge, this is the largest study to date with long-term outcome data of this novel approach. Methods: Three hundred twenty-eight patients who underwent physiologic surgical treatment over a 5.5-year period were evaluated using a prospective database and chart review. Preoperative characteristics, operative details, and postoperative outcomes (volume difference change, Lymphedema Life Impact Scale score) were assessed. Statistical analysis including multivariate regression was performed. Results: Two hundred twenty patients (67.1 percent) underwent simultaneous vascularized lymph node transplant and lymphovenous bypass. Mean body mass index was 26.9 ± 4.7 kg/m 2 . Ninety-two patients (41.8 percent) had lymphedema of the lower extremity, 121 (55.0 percent) had upper extremity involvement, and seven had lymphedema of upper and lower extremities (3.2 percent). Average duration of lymphedema was 95.4 ± 103.6 months. Thirty patients (13.6 percent) had primary lymphedema and 190 patients (86.4 percent) had secondary lymphedema. The majority improved and experienced volume reduction of an average 21.4 percent at 1 year ( p < 0.0001), 36.2 percent at 2 years ( p < 0.0001), 25.5 percent at 3 years ( p = 0.1), and 19.6 percent at 4 years. Median Lymphedema Life Impact Scale scores were 7.0 points lower ( p < 0.0001) at 3 months and improved progressively over time to 27.5 points lower at 3 years postoperatively ( p < 0.005). Conclusions: Simultaneous vascularized lymph node transplant and lymphovenous bypass is an appropriate and effective approach for both early and advanced stages of primary and secondary lymphedema, with significant objective and subjective improvements. Volume reduction in the affected limb was observed at all time points postoperatively, with significant improvement in Lymphedema Life Impact Scale scores. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.